The challenges and acceptance of fresh fruit bunch buyer in purchasing the MSPO certified product case of palm oil mill in Perak / Muhammad Zarul Rizal Muhammad - Muhammad, Muhammad Zarul Rizal (Faculty of Plantation and Agrotechnology, 2019)
Recently, Malaysia have an issue in the oil palm industry on ensure the sustainable production of palm oil product without neglect of environmental and future concern. Between 2013 and 2014 the growth of crude palm oil production was very favourable rising from 19.2 million tons to 19.6 million tons or 2.3% (MPOC, 2015). In this case, the FFB price have suddenly decreasing and give the high impact to the oil palm producer. However, with MSPO certification and dealing with FFB dealers probably can help the oil palm producer to acquire premium price for the FFB. This study focus on challenge of palm oil mill organization and their acceptance in purchasing the MSPO certified product. Regarding that matter, these study aim to estimate the challenge and acceptance among the palm oil mill in purchasing the MSPO certified product. Besides that, this study also is to determine the most dominant factor that influences to purchase the MSPO certified product. The method in conduct this research by distribute questionnaire to the selected palm oil mill organization in Perak. The sample size for this study are 40 palm oil mill organization are randomly selected as a respondents for this study. The questionnaire was sent to the palm oil mill by email or manually spread to the respondent. All the data recorded and analyse by using the Statistical package for Social Science (SPSS) consists of the descriptive analysis and multiple regression. Based on the result obtained , show that the most dominant factor influencing purchasing the MSPO certified product which are the independent variable acceptance with 42.7% while challenge are 31.0% related to purchasing certified product.